2021
DOI: 10.1021/acsaem.1c01690
|View full text |Cite
|
Sign up to set email alerts
|

Taming the Redox Property of A0.5Co2.5O4 (A = Mg, Ca, Sr, Ba) toward High Catalytic Activity for N2O Decomposition

Abstract: Nitrous oxide (N2O) originating from the combustion of fossil fuels causes serious environmental issues. The design and construction of a catalyst with high performance for the removal of N2O remains challenging. Herein, a series of alkaline-earth metal-modified A0.5Co2.5O4 (A = Mg, Ca, Sr, Ba) catalysts were initiated by a hydrothermal protocol, and their catalytic activities for N2O decomposition were systematically investigated by experimental and density functional theory calculation. The results reveal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…That is, the Pr site is also involved in the breaking of the N–O bond. From the free energy profile of the N 2 O decomposition pathway, it can be seen that, when Co 3 O 4 catalyzes the N 2 O decomposition, the energy barrier of O 2 molecule desorption course is the highest, that is, O 2 desorption is the rate-determining step, which is also consistent with the previous results. ,, However, with the doping of single atom Pr, the energy barriers of all elementary reactions are reduced, especially in the O 2 desorption process (from *O intermediate to O 2 ).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…That is, the Pr site is also involved in the breaking of the N–O bond. From the free energy profile of the N 2 O decomposition pathway, it can be seen that, when Co 3 O 4 catalyzes the N 2 O decomposition, the energy barrier of O 2 molecule desorption course is the highest, that is, O 2 desorption is the rate-determining step, which is also consistent with the previous results. ,, However, with the doping of single atom Pr, the energy barriers of all elementary reactions are reduced, especially in the O 2 desorption process (from *O intermediate to O 2 ).…”
Section: Resultssupporting
confidence: 88%
“…This indicates that the ability of Pr course is the highest, that is, O 2 desorption is the ratedetermining step, which is also consistent with the previous results. 21,27,31 In this work, Co 3 O 4 and a series of Pr-doped Co 3 O 4 (Pr/Co molar ratio 0.02−0.15) catalysts were synthesized by a citric acid method (in which a certain amount of urea was added as combustion agent) and applied to the investigation of N 2 O catalytic decomposition. The doping strategy of rare earth elements (such as Y, 31 Ce, 32 Nd, 24 Gd, 15 etc.)…”
Section: Influence Of Prmentioning
confidence: 99%
See 2 more Smart Citations
“…Relevant studies have shown that the appropriate alkali metal could significantly improve the electron transfer property of catalysts and enhance the catalytic decomposition activity of N 2 O. By the addition of potassium (K), a basic source, the electronic structure of Mn x Co 1– x Co 2 O 4 spinel structure catalysts’ surface was optimized by Abu-Zied and co-workers, which consequently enhanced the catalytic decomposition performance of N 2 O . Franken et al found that a small amount of K could stabilize the active sites and fine-tune the redox ability of the Cu 0.25 Co 2.75 O 4 catalyst .…”
Section: Introductionmentioning
confidence: 99%